The impact of the spread of electronic payment methods on the volume of banking deposits: Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to demonstrate the impact of the spread of electronic payment on the volume of bank deposits. The research starts from the problem of the extent to which the spread of electronic payment contributes to changing the volume of bank deposits in the Iraqi banking sector. The research aims to demonstrate the extent of the impact of the spread of electronic payment on the volume of bank deposits in the Iraqi banking sector. The research adopted the quantitative approach in analyzing the financial data for the years (2017 - 2023) by applying it to the banking sector (government - private). The data were analyzed using the statistical program (EVIEWS 13), and indicators were calculated (the number of debit cards, the number of credit cards, the number of prepaid cards, the number of ATMs and their spread rate, the number of points of sale and their spread rate) in measuring the spread of electronic payment. The deposit volume index was also adopted in measuring bank deposits. The research reached several results, the most important of which was the noticeable impact of the spread of electronic payment through its tools represented by (the number of debit cards, the number of credit cards, the number of prepaid cards, the number of ATMs, the number of points of sale) in the growth of the volume of bank deposits in the Iraqi banking sector during the research years).